EFFECTIVENESS OF PLATELET-RICH PLASMA IN ENHANCING SPINAL FUSION: A SYSTEMATIC REVIEW AND META-ANALYSIS - ALHOI HENDRY HENDERSON; SABRI IBRAHIM; ERWIN HANDOKO; SONNY GIAT RAJA SARAGIH; HERICK ALVENUS WILLIM (Coluna/Columna)
ABSTRACT Spinal fusion relies on autologous iliac crest grafts, but complications and nonunion rates ranging from 5% to 43% increase costs and lead to suboptimal outcomes. This meta-analysis evaluated the efficacy of Platelet-Rich Plasma (PRP) in enhancing spinal fusion outcomes. A systematic literature search was conducted in PubMed, Cochrane Library, SagePub, Embase, Web of Science, CINAHL, Medline, and ScienceDirect. Pooled odds ratios (ORs) or weighted mean differences (WMDs) were calculated to assess PRP’s efficacy in improving fusion rates, reducing back pain (as measured by the visual analog scale [VAS]), and assessing adverse events. Meta-analysis was performed via Review Manager 5.4 software. This study is registered with PROSPERO. Four randomized controlled trials involving 152 patients were included. PRP significantly improved bone fusion rates (OR of 3.16, 95% CI = 1.49 to 6.72, p = .003, I2 = 11%) and reduced back pain at 3- and 6-month post-surgery. At 3 months, the VAS score showed a mean difference was -.30 (95% CI: -.47 to -.12; p = .001; I2 = 0%), and at 6 months, the mean difference was -.57 (95% CI: -.75 to -.40; p < .001; I2 = 0%). No significant difference was observed at 12- and 24-month post-surgery, and no adverse effects were reported. The meta-analysis suggests that PRP improves bone fusion and reduces back pain at 3- and 6-month post-surgery without adverse effects. However, its benefits diminish over time, with no significant impact at 12 and 24 months, necessitating further research to assess long-term efficacy. Level of Evidence I; Randomized and Control Clinical Studies.